Absence of direction‐specific cross‐modal visual–auditory adaptation in motion‐onset event‐related potentials. (22nd November 2015) - Grzeschik, Ramona; Lewald, Jörg; Verhey, Jesko L.; Hoffmann, Michael B.; Getzmann, Stephan
Abstract: Adaptation to visual or auditory motion affects within‐modality motion processing as reflected by visual or auditory free‐field motion‐onset evoked potentials (VEPs, AEPs). Here, a visual–auditory motion adaptation paradigm was used to investigate the effect of visual motion adaptation on VEPs and AEPs to leftward motion‐onset test stimuli. Effects of visual adaptation to (i) scattered light flashes, and motion in the (ii) same or in the (iii) opposite direction of the test stimulus were compared. For the motion‐onset VEPs, i.e. the intra‐modal adaptation conditions, direction‐specific adaptation was observed – the change‐N2 (cN2) and change‐P2 (cP2) amplitudes were significantly smaller after motion adaptation in the same than in the opposite direction. For the motion‐onset AEPs, i.e. the cross‐modal adaptation condition, there was an effect of motion history only in the change‐P1 (cP1), and this effect was not direction‐specific – cP1 was smaller after scatter than after motion adaptation to either direction. No effects were found for later components of motion‐onset AEPs. While the VEP results provided clear evidence for the existence of a direction‐specific effect of motion adaptation within the visual modality, the AEP findings suggested merely a motion‐related, but not a direction‐specific effect. In conclusion, the adaptation of veridical auditory motion detectors by visual motion is not reflected by the AEPs of the present study. Abstract : When testing within one modality, adaptation to visual or auditory motion greatly affects the visual or auditory motion‐onset evoked potentials (VEPs, AEPs) to the onset of subsequent motion. Here, we combined both modalities and tested whether adaptation to visual motion affects the auditory motion‐onset response. VEPs and AEPs of 21 subjects were recorded from 57 EEG channels in six blocks. They were analysed for the Scatter, Same‐Direction, and Opposite‐Direction adaptation conditions (see Figure). While the VEP results prooved the existence of a direction‐specific effect of motion adaptation within the visual modality, the AEP findings suggested merely a motion‐related effect.